A164 PATTERNS IN MEDICAL THERAPY AND CLINICAL OUTCOMES IN PATIENTS WITH CONCOMITANT INFLAMMATORY BOWEL DISEASE AND PRIMARY SCLEROSING CHOLANGITIS: A SINGLE CENTRE RETROSPECTIVE ANALYSIS. (4th March 2021) - Donaldson, K; Mitchell, R A; Enns, R A; Bressler, B; Rosenfeld, G; Leung, Y; Ramji, A; Ko, H
Abstract: Background: Inflammatory bowel disease (IBD) in patients with primary sclerosing cholangitis (PSC) is characterized by pancolitis with rectal sparing and is associated with an increased risk of colorectal and biliary malignancies. Currently, pharmacologic management of IBD in the setting of PSC is the same as in IBD alone. Aims: To assess patterns in medical therapy, and incidence of adverse outcomes in patients with concomitant IBD and PSC. Methods: A retrospective review was conducted on all PSC-IBD patients followed between January 2010 and June 2018. The Endoscopic Mayo Score was used to grade IBD severity in PSC-ulcerative colitis (UC). Results: 69 patients were identified, 44 (63.8%) were male. The mean ages of IBD and PSC diagnosis were 28.6 (SD 14.9) and 37.0 (SD 18.9) years, respectively. The median length of follow up was 12 (range 2–49) years. 52 (75.4%) patients had UC, and 17 (24.6%) had Crohn's disease (CD). 28 (87.5%) PSC-UC patients had pancolitis, and 4 (12.5 %) had proctitis. Among those with pancolitis, 8 (28.6%) had relative rectal sparing. 4 (14.3%) patients had more severe inflammation proximally, whereas only 1 (3.6%) had more severe distal inflammation. 23 (82.1%) patients had the same degree of inflammation throughout. 14 (93.3%) PSC-CD patients had colitis/ileocolitis and 1 (6.7%) had ileitis. Among those with PSC-UC, 16 (50.0%), 12 (37.5%), and 4 (12.5%) patients had grade 1, 2, and 3 disease, respectively. 62 (89.9%) PSC-IBD patients were treated with aminosalicylates, and 26 (37.7%) with biologics at some point in their IBD course. 26 (37.7%) were treated with aminosalicylates alone. 4 (5.8%) did not require any IBD therapy. Cholangiocarcinoma, colorectal cancer, and gallbladder cancer developed in 8 (11.6%), 1 (1.4%), and 1 (1.4%) PSC-IBD patients, respectively. 16 (23.2%) patients required partial or total colectomy. Indication for surgery was inflammation or stenosis, dysplasia, and neoplasia in 13 (81.3%), 2 (12.5%), and 1 (6.3%) patients, respectively. Conclusions: The majority of this cohort had UC with mild disease activity. Pancolitis was common, with frequent rectal sparing and more severe right-sided inflammation. Despite the predominance of low-grade colitis, a large portion of patients required treatment with biologics. The incidence of adverse outcomes underscores the need for strict adherence to recommended surveillance practices. Low grade endoscopic activity, typical of the quiescent IBD course in PSC-IBD, may mask low grade histologic inflammation, which in turn may contribute to the increased risk of colonic neoplasia. Further studies are needed to determine the best management strategy for IBD in patients with PSC. Funding Agencies: None